Utilizing Poetry as Spiritual Care for Hospital Staff - Doverspike, Rebecca (Journal of pastoral care & counseling, 2024)
This personal reflection emphasizes the potential benefits of poetry for interfaith spiritual and pastoral support of medical professionals. Details are provided for the implementation of several successful practices, including an Intensive Care Unit Poetry Basket, Portable Poetry with Aromatherapy Towelette Hand Blessings, and Presenting Poems to Nurse Practice Council. The references include the poetry used in the spiritual care activities and the author also provided a helpful “Further Resources” section.